Factors that influence student’s choice in choosing nursing program as their study field : a study at KPTMKB Waterfront Campus / Siti Nadiah Abdullah - Abdullah, Siti Nadiah (2012)
The aim of this study was to examine the factors that contribute to the choice of nursing program at KPTMKB Waterfront Campus. There are four factors that has been studied, which are: career aspirations, socio-economic status, personal ability and parental encouragement. In collecting data, the researcher used both secondary and primary data. The questionnaires had been used in order to get feedback from the students. Researcher had distributed 130 questionnaires to all students at KPTMKB Waterfront Campus. Out of 130, 117 questionnaires was return back. The data collected was tested on its frequency analysis. Further analysis had been done by using reliability analysis. Correlation was used to test the hypotheses in this study as well as regression analysis. The findings of this study show that all independent variables which are career aspirations, socio-economic status, personal ability and parental encouragement have relationship with the choice of nursing program by students. Only two out of four factors which are personal ability and parental encouragement positively influence the choice of nursing program at KPTMKB Waterfront Campus. Another two factors which are career aspirations and socio-economic status not influence the choice of nursing program at KPTMKB Waterfront Campus. From the result obtained in this study, researcher suggests some recommendations that can help KPTMKB Waterfront Campus to improve their service and at the same time increase the student enrollment